Changes in Circulation and Particle Scavenging in the Amerasian Basin of the Arctic Ocean over the Last Three Decades Inferred from the Water Column Distribution of Geochemical Tracers. Issue 12 (18th December 2019) - Grenier, Melanie; François, Roger; Soon, Maureen; Rutgers van der Loeff, Michiel; Yu, Xiaoxin; Valk, Ole; Not, Christelle; Moran, S. Bradley; Edwards, R. Lawrence; Lu, Yanbin; Lepore, Kate; Allen, Susan E.
Abstract: Since the 1980–1990s, international research efforts have augmented our knowledge of the physical and chemical properties of the Arctic Ocean water masses, and recent studies have documented changes. Understanding the processes responsible for these changes is necessary to be able to forecast the local and global consequences of these property evolutions on climate. The present work investigates the distributions of geochemical tracers of particle fluxes and circulation in the Amerasian Basin and their temporal evolution over the last three decades (from stations visited between 1983 and 2015). Profiles of 230‐thorium ( 230 Th) and 231‐protactinium ( 231 Pa) concentrations and neodymium isotopes (expressed as εNd ) measured in the Amerasian Basin prior to 2000 are compared to a new, post‐2000s data set. The comparison shows a large scale decrease in dissolved 230 Th and 231 Pa concentrations, suggesting intensification of scavenging by particle flux, especially in coastal areas. Higher productivity and sediment resuspension from the shelves appear responsible for the concentration decrease along the margins. In the basin interior, increased lateral exchanges with the boundary circulation also contribute to the decrease in concentration. This study illustrates how dissolved 230 Th and 231 Pa, with εNd support, can provide unique insights not only into changes in particle flux but also into the evolution of ocean circulation and mixing. Plain Language Summary: The Arctic Ocean is one of the oceanic regions most affected by climate change. The increasing summer retreat of sea ice allows greater atmosphere‐ocean exchanges and light penetration, while land‐ocean exchanges are expected to increase, due to enhanced continental erosion (notably through permafrost thawing and increased river flow). These changes are driven by climate and in turn impact the climate. This study aims at assessing possible shifts in oceanic circulation and particle fluxes resulting from these climate‐driven changes in the Amerasian Basin of the Arctic Ocean, during the last few decades. To achieve this goal, we measured geochemical tracers of circulation and particle fluxes in seawater samples collected in this area between 2005 and 2015, which we compared to published data from samples collected between 1983 and 2000. The primary geochemical tracers studied here are 230 Th and 231 Pa. These radioisotopes are uniformly produced in seawater, from uranium decay, and are strongly reactive with particles. Therefore, their oceanic distribution depends on particle fluxes and circulation. The evolution of their distribution in the Amerasian Basin over space and time documents enhancement of particle flux and lateral mixing in the Amerasian basin of the Arctic Ocean over the last three decades. Key Points: Concentration decreases of 230 Thd and 231 Pad suggest an enhancement of particulate scavenging since the 2000s in the Amerasian Basin Particulate scavenging results from higher productivity and sediment resuspension from the shelves Post‐2000s changes in intermediate and deep layers suggest enhanced lateral mixing between the margins and central areas of the basins